(2S,4S)-4-azido-1-benzyl-2-[(S)-2,2-dimethyl-1,3-dioxolan-4-yl] pyrrolidine - Chesterton, A; Jenkinson, S; Jones, N; Fleet, G; Watkin, D (2006)
The relative stereochemistry of the title compound, C16H 22N4O2, a key intermediate in the synthesis of 3-deoxy imino sugars, was firmly established by X-ray crystallographic analysis. The absolute configuration was inferred from the starting material, D-galactose. There are no unusual crystal packing features. © 2006 International Union of Crystallography. All rights reserved.